The clinical features and therapy of community-acquired gram negative bacteremia in children less than three years old - Kuang-Che Kuo; Yi-Chun Yeh; I-Min Chiu; Kuo-Su Tang; Chih-Min Su; Ying-Hsien Huang (Pediatrics and Neonatology)
Background: Community-acquired Gram-Negative (GN) bacteremia caused more morbidity and mortality recently in children. The increasing drug resistance was also an important issue. However, published reference was few about children. Methods: We conducted a retrospective study to collect febrile patients with blood culture from a pediatric emergency department during 2007∼2013, and exclude cases ever admitted to hospital within 14 days. These blood cultures all showed single GN organism. The demographic characteristics of enrolled patients and the antibiogram of pathogens were recorded, and then were compared statistically to find out the immediate and appropriate antibiotics. Results: Total 143 sets of blood culture were GN bacilli and the median age of cases was 2 (IQR, 1-5) years old. Male gender was predominant. Non-fermenting Gram-negative bacilli group (NFGNB spp.), Salmonella spp. and Escherichia coli were first three common pathogens respectively. However, total 37 cases of NFGNB spp. other than Pseudomonas aeruginosa were the possible pathogens. By multiple logistic regression analysis, lower hemoglobin and higher alanine aminotransferase were significant difference between common pathogens and possible ones. Besides, the prevalent age regarding resistant strains of Escherichia coli and Pseudomonas aeruginosa were both focused on less than 1 year old. However, Salmonella spp. were prevalent in the age from 1 to 3 years old. Conclusions: For different age groups, Salmonella spp. and Escherchia coli were the most common pathogens of community-acquired GN bacteremia. For infants, Pseudomonas aeruginosa sepsis and resistant strain of Escherchia coli should be alert, and broader antibiotics should be considered. Key Words: community-acquired, bacteremia, gram-negative bacilli, infants